(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to design a proposed operational framework for integrating environmental sustainability skills and augmented intelligence competencies into the higher education environment, specifically targeting the promotion of a transition toward "Green Education" through the Center for Entrepreneurship and Innovation at AL Zintan University as a future roadmap. The research addresses a distinct conceptual and practical gap characterized by the absence of an operational mechanism linking academic curricula with entrepreneurial developmental activities, where technology is often taught in isolation from environmental responsibility. To achieve this objective, the study adopts a descriptive-analytical approach based on a systematic induction method, reviewing recent literature and previous studies published between 2020 and 2026. The researcher utilizes three primary methodological tools: content analysis, a strategic situational analysis of the local environmental and technical context of AL Zintan University, and innovative modeling to delineate structural roles and operational pathways. The findings demonstrate an alignment gap in higher education institutions due to the segregation of emerging technologies from data protection and environmental duties. Furthermore, the study concludes that the success of the twin transition at Alzintan University hinges on reducing financial constraints through local partnerships and building "cybersecurity resilience" to protect the digital ecosystem. Consequently, the study culminates in designing an innovative structural framework to govern the initiative’s paths using the Responsibility Assignment Matrix (RACI) across three interconnected, cyber-secured operational tracks: (Experiential Learning and Training Track, Smart-Green Incubator Track, and Governance and Cyber Resilience Track). The study recommends that the administration of Alzintan University officially adopt this proposed initiative, launch collaborative green incubators across faculties, and update internal legislative policies to enhance digital sovereignty and safeguard intellectual property.